Determinant Factors Affecting The Quality of Basic Education Services: A Standard Pattern From Regional Government Experience - Said, Moh; Cahyasari, Erlita; Winoto, Suhartono; Widodo, Nurjati; Muslim, Abd Qadir (Universitas Sultan Ageng Tirtayasa, 2024)
Basic education is the foundation for the development of a nation. However, the implementation of basic education services in Indonesia is not yet fully running well. Shifting the authority to provide basic education to regional governments is a challenge for regional governments. Bonding lack of capacity and territorial catchment complicates the problem of providing basic education services. This research examines the factors that influence the quality of basic education service delivery in Banyuwangi Regency, Indonesia. This research uses a systems thinking approach. Modeling with a causal loop diagram as a type of qualitative system model that illustrates the factors that influence the capacity of basic education service delivery. The causal loop diagram was constructed through in-depth interviews with several informants, namely the head and secretary of the education office, elementary and middle school principals, elementary and middle school teachers, and community members (n=12), and FGD (n=2). The location of this research is Banyuwangi Regency, the area with the largest area in East Java. Research findings show that the factors influencing the quality of basic education service delivery in Banyuwangi Regency are based on CLD. A model consisting of two nodes balancing that interact in such a way that the activity of one loop significantly reduces the balance of other loops in an effort to achieve a goal. That the quality of providing basic education services is balanced by conditions of service gaps, so the following actions need to be taken: a) when performance decreases, then check whether this happens because the targets that have been made have been lowered, then b) check how the targets were made and who determines it. This means that the quality of basic education services in Banyuwangi Regency can be improved by evaluating whether the target setting is realistic with the quality of educational facilities and infrastructure, the quality of transportation infrastructure, and the geographical location, which varies according to the characteristics of the region.